2018
DOI: 10.1002/vjch.201800082
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the adsorption of organic molecules on rutile TiO2 (1 1 0) surface: A theoretical study

Abstract: We investigated the adsorption of formic, acetic, benzoic acids, phenol, nitrobenzene molecules on rutile-TiO 2 (1 1 0) surface using the density functional theory (DFT) calculations. Details of the interaction between the investigated molecules and rutile-TiO 2 (1 1 0) surface were thoroughly considered by using the charge transfer and atoms in molecules analyses. The most stable configurations have been found upon adsorption of these molecules on TiO 2 surface by employing the Perdew-Burke-Ernzerhof (PBE) fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
3
0
3
Order By: Relevance
“…Tri et al . (70) showed that the electrostatic attraction in the form of [Ti…OH 2 ] and strong hydrogen bond in the form of [HO…H 2 O] cause stable adsorption configurations. They also determined the adsorption processes of the mentioned molecules are chemisorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tri et al . (70) showed that the electrostatic attraction in the form of [Ti…OH 2 ] and strong hydrogen bond in the form of [HO…H 2 O] cause stable adsorption configurations. They also determined the adsorption processes of the mentioned molecules are chemisorption.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the organic molecules can also interact with the TiO 2 surface. Tri et al (70) showed that the electrostatic attraction in the form of [Ti. .…”
Section: Basics Of the Mechanism Of Dye Degradationmentioning
confidence: 99%
“…The substituent effect in these complexes has less impact on their adsorption models. Similarly, the adsorption of formic acid, acetic acid, benzoic acid, phenol, nitrobenzene molecules on the rutile TiO 2 (110) surface was investigated by Tri et al 265 The calculated adsorption energies are in the range of À18.5 to À28.8 kcal/mol, and the interactions mostly arise from the TiÁÁÁO dative bond and O HÁÁÁO strong hydrogen bond. The interactions between the adsorbed molecules on the rutile TiO 2 (110) surface are stronger for the COOH groups than for the OH or NO 2 groups.…”
Section: Adsorption Patterns Of Aldehydes Acetone Acetate and Acidsmentioning
confidence: 99%
“…Kết quả này phù hợp với các khảo sát trước đây về sự hấp phụ các phân tử kháng sinh trên bề mặt TiO2 [11]. Ngoài ra, các kết quả thu được trong nghiên cứu này có sự tương quan tốt với các nghiên cứu trước đây khi khảo sát sự tương tác giữa các phân tử với bề mặt r-TiO2 [11,20,21]. Cụ thể, các kết quả tính toán cho thấy các giá trị ρ(r) tại các BCP Ti5f‧‧‧O, H‧‧‧Ob trong phức bền nhất SFX-4 nhỏ hơn trong các phức bền nhất giữa AP, AX, TC với r-TiO2 [11].…”
Section: Năng Lượngunclassified
“…Kết quả cho thấy ở các phức hình thành các phân tử SFX có xu hướng sắp xếp theo chiều ngang, trải rộng lên trên bề mặt r-TiO2 tại các vị trí Ti5f và Ob trong sự hình thành các tương tác bề mặt giữa Ti5f‧‧‧O/N và H‧‧‧Ob. Các khoảng cách tương tác ngoại phân tử này tương ứng trong khoảng 2,24-2,47 Å và 1,76-2,71 Å. Các giá trị này đều nhỏ hơn tổng bán kính van der Waals của hai nguyên tử tham gia tương tác (rvdW(O-H) = 2,72 Å; rvdW(Ti-O) = 3,39 Å; rvdW(Ti-N) = 3,42 Å), và phù hợp với các công bố trước đây về sự hình thành các tương tác giữa Ti5f‧‧‧O và H‧‧‧Ob trong các phức giữa các phân tử hữu cơ, kháng sinh với bề mặt TiO2[11,12,20,21]. Các cấu trúc bền của sự hấp phụ SFX trên bề mặt r-TiO2 (đơn vị khoảng cách Å) Bên cạnh đó, nhiều tương tác kiểu Ti5f‧‧‧O/N và N/C-H‧‧‧Ob xuất hiện ở các cấu trúc SFX-1 và SFX-4, nhiều hơn so với ở các phức SFX-2, SFX-3.…”
unclassified